Development of an elisa test for the serodiagnosis of typhoid infections - Nevhutalu, Prinsloo Azwitevhelwi (My University, 1983)
Refer to the document
Thesis (M.Sc.( Medical Sciences)) --University of the North, 1983
Keywords: Elisa test; Typhoid infections; Typhoid fever -- Diagnosis